Science Under Political Change: The Experience of Russian Genetics in the 1960s - S. V. Shalimov (Vestnik MGIMO-Universiteta)
Abstract: The paper is devoted to the development of Soviet genetics in the higher school in the second half of the 1960s. Currently history of Russian genetics is becoming a popular research subject among Russian and foreign historians. Tragic events, which befell Soviet genetics in mid 20th century have been thoroughly examined both in scientific and popular accounts. Thus development of genetics during the later period of Soviet history makes a more suitable subject for a rigorous historical investigation. In the late 1960s Soviet science and technology policy in regard to biological research was aimed at the restoration of losses suffered due to the rise of Lysenkoism. This period has not yet been duly investigated and there are almost no publications authored by professional historians dedicated to genetics research in the Soviet Union in the 1960-80s. To a certain extent this gap has been covered in the author’s earlier publications. The research is based on the wide range of archive documents from the archives of Moscow, Saint- Petersburg and Novosibirsk. Also, significant place is given to oral sources. The paper underlines that Leningrad and Novosibirsk Universities made a great contribution to the revival of human resources in the Soviet genetics. At the same time many other biological departments and institutes were going through the reorganization of the Soviet biology with lots of difficulties. The examples of the All-Union Institute of Plant Industry of the VASKhNIL and the Novosibirsk agricultural institute vividly illustrated that Lysenkoists still held an important positions in the field of science and education. Besides, the lack of material supplies of the chairs and laboratories had a destructive influence.